Novel EPG5 Mutation Associated with Vici Syndrome Gene - Frouzandeh Mahjoubi; Samira Shabani; Sogand Khakbazpour; Aylar Khaligh Akhlaghi (Case Reports in Genetics)
Introduction. Vici syndrome (also known as immunodeficiency with cleft lip/palate, cataract, and hypopigmentation and absent corpus callosum) is considered as a progressive neurodevelopmental multisystem disorder. Till date, only 80 cases, including our patient, with this syndrome have been reported .This syndrome is characterized by agenesis of the corpus callosum, hypopigmentation of the eyes and hair, cataract, cardiomyopathy, combined immunodeficiency, hearing loss, seizures, and additional multisystem involvements which have been reported as case reports in the past. Clinical Manifestation. A 5-year-old girl, who is a product of consanguineous marriage, was referred to our center with developmental delay, optic atrophy, blindness, spasticity, seizure, movement disability, and spasticity. Her magnetic resonance imaging (MRI) test showed agenesis of the corpus callosum and her metabolic test reported normal. Materials and Methods. In our laboratory, blood sample was obtained from the patient. DNA was extracted from lymphocytes, and whole exome sequencing (WES) using next generation Illumina sequencing was performed. Result. A novel (private), homozygous, nonsynonymous mutation c.A3206G (p.Y1069C Het) in EPG5 gene was detected; in continuum, testing for this specific variant in her parents was carried out. DNA sequencing of the PCR-amplified product of the EPG5 exon 17 showed that her parents were heterozygote for this variant. These mutations have not been reported before and therefore classified as variation of unknown significance (VUS). Mutation in this gene is shown to cause autosomal recessive Vici syndrome. Conclusion. Since clinical features of Vici syndrome has overlap, its diagnosis is differential and developmental delay occurs in 98% of reported cases. Vici syndrome can be considered as one of the main causes of developmental delay, and this syndrome can be introduced as a novel group of inherited neurometabolic conditions and congenital disorders.